Herring roe oil exerts immunomodulatory effects on the IL-17/23 signaling axis in immune and skin cells as models for psoriasis - Jennifer Mildenberger; Nina Therese Solberg; Tone-Kari K. Østbye; Vibeke Høst; Federico Petruccelli; Runhild Gammelsaeter; Sissel B. Rønning; Mona E. Pedersen (Frontiers in Medicine, 2026)
Several systemic treatment options are available for moderate to severe psoriasis, while low-risk oral treatments for milder forms are limited. Herring roe oil has previously shown beneficial effects on the clinical presentation of psoriasis, however, cell-specific effects remained unknown. This study aimed to elucidate cellular effects of herring roe oil and whether signaling pathways in skin and immune cells relevant to the pathophysiology of psoriasis are affected by herring roe oil. We used cell-culture models of human primary macrophages and T-cells, a keratinocyte cell line and human primary fibroblasts to represent important site-specific pathological aspects of psoriasis in the skin and immune system. The cells were supplemented with herring roe oil emulsions and cellular signaling was analyzed on protein and mRNA level. Skin cell proliferation was analyzed in real-time by a Live-Cell Analysis System. We here present results which suggest that herring roe oil exerts effects on different cell types on major psoriasis-driving aspects, reducing the secretion of IL-23 and IL-17 from macrophages and T-cells, respectively. Herring roe oil also interfered with IL-17-induced expression of the psoriasis marker S100A7 and limited the proliferation of keratinocytes in co-culture with fibroblasts. Our results on cellular effects of herring roe oil demonstrate relevance in immunomodulating pathways known to be of importance in psoriatic pathophysiology and are in line with the potential clinical use of herring roe oil in the treatment of psoriasis.